2019
DOI: 10.14254/2071-8330.2019/12-1/14
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance practices on firm’s performance: An empirical evidence from Indian tourism sector

Abstract: The growth of Indian companies in recent years has led to a change in the nature of the economy which attracted outsider investors from developed countries who demanded robust corporate governance practices from Indian companies which made regulators and competitors gave a great effort to restructure corporate governance. Therefore, this paper aims to investigate the effect of corporate governance practices on firms' performance, with a special reference to the Indian tourism sector. The study uses a panel dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 66 publications
2
45
2
1
Order By: Relevance
“…When the number of directors on the board is big, firms would gain more arrive to many resources in comparison to the case when board size is small. The bigger board of directors, the more skilled, practiced and knowledgeable people be ready which could result in more accurate learning, decision making process and eventually preferable firm performance (Yameen, et al, 2019). BORDEL: Board of directors' diligence is expressed by the number of board meeting; the recurrence of meetings is the time devoted for controlling management.…”
Section: Dependent Variablementioning
confidence: 99%
See 2 more Smart Citations
“…When the number of directors on the board is big, firms would gain more arrive to many resources in comparison to the case when board size is small. The bigger board of directors, the more skilled, practiced and knowledgeable people be ready which could result in more accurate learning, decision making process and eventually preferable firm performance (Yameen, et al, 2019). BORDEL: Board of directors' diligence is expressed by the number of board meeting; the recurrence of meetings is the time devoted for controlling management.…”
Section: Dependent Variablementioning
confidence: 99%
“…It was concluded that when board members meet more repeatedly, the performance becomes better as a result. Board meetings are very fundamental for directors as they utilize the attendance as a way which enables them to control properly (Yameen, et al, 2019). ACSIZE: Audit committee is one of the essential elements that occupied an important position in reinforcement firms' performance, it provides a sufficient safety against fraud and makes sure that these securities are in related with the best practices.…”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…The financial performance of the companies is said to be linked with the composition of board, however, with respect to the industries, the dynamism differ [21] [22]. The linear association of one variable tested using correlation with another variable [23].…”
Section: Analysing Nexus Of Board Composition With the Financial Perfmentioning
confidence: 99%
“…Thus, managers intend to develop their business on new social and environmental coordinates as a result of the integration of social responsibility elements (Kaasa, 2019). Recent studies (Dobrovik et al, 2018;Gablas et al, 2018;Kovacs and Kot, 2016) and surveys (Yameen, 2019;Derun and Mysaka, 2018;Meyer and Meyer, 2016) have certified that corporate social responsibility is for many multinational companies and transnational corporations an intrinsic component of their strategies and policies, and for others a clearly defined goal that, once achieved, can produce certain economic and image benefits. More and more teams of corporate managers understand that business growth does not mean only profit increase, that the growth is relative if it does not integrate CSR-defining elements.…”
Section: Introductionmentioning
confidence: 99%